Exercising in a hot environment: Which t-shirt to wear? - Sperlich, B.; Born, D.-P.; Lefter, M. D.; Holmberg, H. C. (Wilderness and Environmental Medicine, 2013)
Objective: The aim of this study was to investigate thermoregulatory, cardiorespiratory, metabolic, and perceptual responses while running in a hot environment (31.7° ± 1.0°C; 42% ± 3% relative humidity) and wearing T-shirts made from different fiber types. Methods: Eight well-trained men performed 4 tests wearing either a T-shirt made of 100% polyester with 4, 6, or 8 channels, or one made of 100% cotton. Each test consisted of 30 minutes running at 70% of peak oxygen uptake, followed by a ramp test to exhaustion and 15 minutes of recovery. Results: There were no differences in skin, core, and body temperatures between fiber types during submaximal and high-intensity running (best P = .08). During recovery, body temperature and shivering/sweating sensations were lower when wearing 4- and 6-channel fibers (P < .04) compared with cotton. The relative humidity at the chest and back were lower for all polyester T-shirts compared with cotton during and after submaximal and maximal running (P < .007). Heart rate (best P = .10), oxygen uptake (P = .95), respiratory exchange ratio (best P = .93), ventilation (best P = .99), and blood lactate concentration (best P = .97) did not differ between the fiber types. Nor were any differences in time to exhaustion (best P = .76), ratings of perceived exertion (best P = .09), thermal sensation (best P = .07), or sensation of clothing wetness (best P = .36) discovered. Conclusions: Although statistical analysis revealed lower shivering/sweating sensations while wearing 4- and 6-channel fiber shirts during recovery, with an improved chest and back microenvironment for all polyester T-shirts, the question remains whether these differences are of any practical relevance because the performance of the well-trained men was unaffected.